Pengaruh Literasi Keuangan dan Modal Sosial Terhadap Keberlangsungan Usaha (Studi Empiris Pada UMKM Makanan di Kabupaten Magelang) - Zaki Fu'adi; Friztina Anisa (Universitas Muhammadiyah Magelang, 2022)
This study aims to test and analyze financial literacy and social capital on business continuity. The sample in this study was 100 respondents with purposive sampling method. This study uses quantitative methods with descriptive test analysis, validity and reliability tests, multiple linear regression analysis and hypothesis testing with the help of the SPSS version 18 program. The results of this study state that Financial Literacy has a positive and significant effect on business continuity, Social Capital has a positive influence. and significant to Business Continuity, and Financial Literacy and Social Capital together have a positive and significant impact on Business Continuity.